(untitled) (Scientific journal of the Fergana State University, 2026)
In the article, it was proved that the scholar’s “Maktubat” is important for the treatment of newly emerging fake orders, their activities that worry the society, including the activities of some undeserving sheikhs and the indulgence of their murids in unreasonable actions. Moreover, in relation to the activities of religious communities that dance and chant, which are spreading on social networks, it is stated in the work “Maktubat” Naqshbandi, sheikhs did not consider sa’mo and dancing permissible.